2001
DOI: 10.1186/1472-6750-1-5
|View full text |Cite
|
Sign up to set email alerts
|

Mannosylerythritol lipid, a yeast extracellular glycolipid, shows high binding affinity towards human immunoglobulin G

Abstract: Background: There have been many attempts to develop new materials with stability and high affinity towards immunoglobulins. Some of glycolipids such as gangliosides exhibit a high affinity toward immunoglobulins. However, it is considerably difficult to develop these glycolipids into the practical separation ligand due to their limited amounts. We thus focused our attention on the feasible use of "mannosylerythritol lipid A", a yeast glycolipid biosurfactant, as an alternative ligand for immunoglobulins, and … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
13
0

Year Published

2008
2008
2022
2022

Publication Types

Select...
4
3

Relationship

1
6

Authors

Journals

citations
Cited by 29 publications
(14 citation statements)
references
References 37 publications
(47 reference statements)
0
13
0
Order By: Relevance
“…PuriWcation of glycoprotein MEL-A, -B and -C exhibit high binding aYnity to human immunoglobulins [15,16,39,43]. They also show binding aYnity towards Ig M and other glycoproteins.…”
Section: Mel Induces Cell Diverentiation and Apoptosismentioning
confidence: 95%
See 1 more Smart Citation
“…PuriWcation of glycoprotein MEL-A, -B and -C exhibit high binding aYnity to human immunoglobulins [15,16,39,43]. They also show binding aYnity towards Ig M and other glycoproteins.…”
Section: Mel Induces Cell Diverentiation and Apoptosismentioning
confidence: 95%
“…They can be used in the treatment of schizophrenia or diseases caused by dopamine metabolic dysfunction [67,72] and microbial infections [37]. MELs are used in the puriWcation of lectins (Immunoglobulin G) [9,15,16,21,39] and in the preparation of ice-slurry as an antiagglomeration agent [41,42]. Self-assembling properties [17-20, 39, 43, 70] of MELs are of recent interest because this behavior could be leveraged in gene transfection and drug delivery [23,24,42,43,65,66].…”
Section: Mel: Why?mentioning
confidence: 99%
“…These MELs exhibit not only excellent interfacial properties [12], but also remarkable differentiation‐inducing activities against human leukaemia cells [13,14], rat pheochromocytoma [15] and mouse melanoma cells [16,17]. MELs also show high binding affinity towards different immunoglobulins and lectins [18–23]. In addition, MEL‐A, the major component of MELs, dramatically increases the efficiency of gene transfection mediated by cationic liposomes [24–27].…”
Section: Melsmentioning
confidence: 99%
“…Previously Im et al [21] reported that MEL‐A shows high binding affinity towards human IgG. The binding behaviour was further investigated by using surface plasmon resonance and the measurement of surface pressure (π)–area ( A ) isotherms [23].…”
Section: Binding Affinity Towards Immunoglobulins and Lectins Of Melmentioning
confidence: 99%
“…1 Several chromatographic techniques including high performance, size exclusion, ion-exchange, hydrophobic interaction, hydroxyapatite, and thiophilic have been used for the purification of immunoglobulins. [2][3][4][5] However, immunoglobulins are often purified by protein A affinity chromatography due to its high selectivity.…”
Section: Introductionmentioning
confidence: 99%